Distribution of Metals along Simiyu Wetland of Lake Victoria Basin and its Impact on Agriculture - Henry, Leonia; Mamboya, Florence Alex (Journal of Wetlands Ecology, 2012)
More than 70% of communities living along Simiyu wetland area are agriculturalists and pastoralists. Physical land degradation and poor nutrient mobility within the soil-plant system have shown a notable impact on agricultural production. Cycling of selected and their impact on agriculture were investigated along Simiyu wetland. Cation Exchange Capacity (CEC) of the soil was studied with respect to soluble cations and selected trace metals. To study the longitudinal and spatial distribution of the selected metals along Simiyu wetland, samples (water, sediments and soil) were taken in three stations along the river namely Bariadi Bridge, Simiyu Bridge and the Simiyu River mouth. Sampling of soil was done at different distances from the river so as to study the flow pattern of the metals and hence to explain the direction of cycling. Sampling was done both inn wet and dry seasons to study the seasonal variation of the metals. Geographical Position System was used to locate the sampling points for soil and water/sediment. Metals Chromium (Cr), Lead (Pb), Zinc (Zn), Coper (Cu), Cadmium (Cd) and Manganese (Mn) analyses were analyzed by atomic absorption spectrophotometer (AAS). High levels of Manganese and Zinc were detected in most samples with different distribution behavior between water and sediments that may reflect difference in solubility of metals in water or possible complex formation of the metals resulting to potentially less solubility of metals, hence retarding their bioavailability to plants low cation exchange capacity. Retarded nutrient mobility in clay soils was observed facilitated by the formation of hard pans resulting to less availability of the nutrients to plants. The study suggests some ways in which farmers can improve soil cation exchange capacity and hence improve agricultural productivity. DOI: http://dx.doi.org/10.3126/jowe.v6i0.5967 J Wet Eco 2012 (6): 31-43